2020
DOI: 10.1097/phm.0000000000001439
|View full text |Cite
|
Sign up to set email alerts
|

STAR—Sonographic Thigh Adjustment Ratio

Abstract: Objective The aim of the study was to explore an individualized sonographic muscle thickness ratio and its cutoff values in the diagnosis of sarcopenia. Design A total of 326 community-dwelling adults were included in this cross-sectional study. Total skeletal muscle mass was evaluated by bioelectrical impedance analysis, and nine-site muscle thickness measurements using ultrasound. Isometric handgrip and knee extension strengths were assessed. Physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…We congratulate them for taking notice on ultrasound (US) measurements in the diagnosis of sarcopenia. Since sarcopenia affects regional rather than total muscle mass and, additionally, as fat mass in obese individuals can affect the total measurements, we agree with the authors in regard to the convenient and prompt use of US for regional measurements 2 . However, we need to make some comments concerning their study design.…”
supporting
confidence: 62%
“…We congratulate them for taking notice on ultrasound (US) measurements in the diagnosis of sarcopenia. Since sarcopenia affects regional rather than total muscle mass and, additionally, as fat mass in obese individuals can affect the total measurements, we agree with the authors in regard to the convenient and prompt use of US for regional measurements 2 . However, we need to make some comments concerning their study design.…”
supporting
confidence: 62%
“…Sarcopenia is the age-related loss of muscle mass and function as well as a significant determinant of physical frailty. 8 Sarcopenia is a major global health problem that is highly common in elderly. It has been suggested that the classical RAS pathway plays an essential role in mechanisms causing muscle wasting in chronic disease states.…”
Section: How and Why Is The Current Article Relevant For Physiatristsmentioning
confidence: 99%
“… 12 , 13 It has been found that ACEI users had higher lower limb muscle mass than those using other antihypertensive drugs. 8 Additionally, continuous use of ACEIs have been found preventive in terms of gait speed and knee extensor muscle strength after a 3-year follow-up. 12 , 13 …”
Section: How and Why Is The Current Article Relevant For Physiatristsmentioning
confidence: 99%
“…Herein, sarcopenia can be defined as the age-related loss of muscle mass and function, which is the physical determinant of frailty. 1 Frailty refers to the multisystem impairment related to increased susceptibility to endogenous or exogenous stressors and infections. In this sense, preventive treatments (eg, vitamin D and exercise) for sarcopenia and frailty are noteworthy during the longlasting quarantine days of COVID-19.…”
mentioning
confidence: 99%